Analisis faktor-faktor yang memengaruhi kinerja karyawan dalam kegiatan pembibitan sawit - Angela, Elsa; Nefri, John; Putra, Vicka Pramudya (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study investigates the impact of leadership style, workplace environment, supervisory support, employee motivation, and individual competencies on staff performance at PT. BTN nurseries. Utilizing a quantitative research design, data were collected through questionnaires distributed to all 30 employees (saturated sampling). The data were then analyzed using statistical methods to explore the relationships between these variables. The results indicate that the combined factors of leadership style, work environment, supervisory support, motivation, and competence have a significant influence on employee performance. Specifically, leadership style was found to have a positive correlation with performance. At the same time, supervisory support appeared to have an inverse relationship with the outcome. Together, these factors account for a considerable portion of the variation in performance among nursery staff. These findings provide valuable insights for organizational management in agricultural contexts, particularly in terms of personnel development and workplace optimization.